2015
DOI: 10.1186/s12931-015-0273-8
|View full text |Cite
|
Sign up to set email alerts
|

Childhood pneumonia increases risk for chronic obstructive pulmonary disease: the COPDGene study

Abstract: BackgroundDevelopment of adult respiratory disease is influenced by events in childhood. The impact of childhood pneumonia on chronic obstructive pulmonary disease (COPD) is not well defined. We hypothesize that childhood pneumonia is a risk factor for reduced lung function and COPD in adult smokers.MethodsCOPD cases and control smokers between 45–80 years old from the United States COPDGene Study were included. Childhood pneumonia was defined by self-report of pneumonia at <16 years. Subjects with lung diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 32 publications
1
74
0
1
Order By: Relevance
“…Similarly, a reduction of lung function by 0.17 litre (0.02 to 0.32) and higher mortality due to COPD in adults was observed in adults who had bronchitis or pneumonia in infancy [32]. This apparent association of childhood pneumonia in COPD development and severe COPD exacerbations [31] may relate to possible reduction in lung growth due to pneumonia [32] and also to inadequate treatment of pneumonia [33]. Regarding acute exacerbations of COPD, a study involving 1,114 subjects over 40 years of age from Korea identified that the exacerbation rate was many times higher (18-fold, p < 0.001) in COPD patients who had a previous history of pneumonia compared to patients who were not affected by pneumonia [34].…”
Section: Pneumonia and Tuberculosis As Potential Precursors To Copdmentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, a reduction of lung function by 0.17 litre (0.02 to 0.32) and higher mortality due to COPD in adults was observed in adults who had bronchitis or pneumonia in infancy [32]. This apparent association of childhood pneumonia in COPD development and severe COPD exacerbations [31] may relate to possible reduction in lung growth due to pneumonia [32] and also to inadequate treatment of pneumonia [33]. Regarding acute exacerbations of COPD, a study involving 1,114 subjects over 40 years of age from Korea identified that the exacerbation rate was many times higher (18-fold, p < 0.001) in COPD patients who had a previous history of pneumonia compared to patients who were not affected by pneumonia [34].…”
Section: Pneumonia and Tuberculosis As Potential Precursors To Copdmentioning
confidence: 82%
“…Hayden and colleagues in recent study of 10,192 adult current and former smokers, concluded that development of adult respiratory disease is influenced by childhood respiratory infections whereby childhood pneumonia was identified as a predictor of COPD (OR 1.40, 95% CI: 1.17-1.66) [31]. Similarly, a reduction of lung function by 0.17 litre (0.02 to 0.32) and higher mortality due to COPD in adults was observed in adults who had bronchitis or pneumonia in infancy [32].…”
Section: Pneumonia and Tuberculosis As Potential Precursors To Copdmentioning
confidence: 99%
“…Pneumonia is less common in adults, although smokers are a subpopulation known to experience increased rates of pneumonia (3)(4)(5). Our previous investigations have demonstrated that pneumonia in childhood is a risk factor for chronic obstructive pulmonary disease (COPD), reduced lung function, and airway disease on chest computed tomography scans in adult smokers (6). This variability in the prevalence of childhood pneumonia and its association with an increased risk of lung disease later in life suggest some underlying genetic susceptibility.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Pneumonia was defined by subject selfreport, as described previously (6). The subjects were classified as having childhood pneumonia if their first episode was at ,16 years of age or during childhood, and lifetime pneumonia if they had ever had pneumonia.…”
Section: Case Identificationmentioning
confidence: 99%
“…The results of the Drakenstein study add urgency to this task. LRTIs are known to be associated with the subsequent development of chronic pulmonary disease (10,11), which is one of the most frequent causes of early death in adults. The data presented here strongly suggest that the association may be causal.…”
mentioning
confidence: 99%